Cineclube Antonio das Mortes and its independent film production - Campos, Marina da Costa (2014)
This article analysis the production of experimental films made by Cineclube Antonio das Mortes (CAM) in 1980, in Goiania, Through the term "independent film". This work is an initial study, therefore, it’s intended, first, to discuss the various conceptions given to “independent cinema” in Brazilian cinema history, from the late 1940s until 1980. Then, this work will try to understand how this production of this Cineclube approaches or moves away from the different conceptions that this term has acquired over the decades.